Knowledge, Attitude and Perception of Medical Students Regarding Community- Oriented Research - Majumdar, Anindo; Kumar S, Ganesh; Roy, Gautam (National Journal of Community Medicine, 2015)
Objective: Objective of the study was to assess the knowledge, attitude and perception of medical students regarding communi- ty-oriented research. Method: This was a cross-sectional study conducted among all 5th semester MBBS students of a teaching hospital in Puducherry. A field-based community-oriented research project was carried out by the students as a part of their routine block posting. At the end of the posting, a self-administered questionnaire was adminis- tered to the students to collect data. Results: Out of total 52 students, 43 (82.7%) completed the study. Less than 50% students answered the questions correctly in areas related to stages of an investigation, hypothesis testing, sample size calculation, data entry and analysis software, and scales of measurement. Performance in study designs and sampling tech- niques were also not satisfactory. Most of the students had a posi- tive attitude towards community-oriented research projects and majority perceived them as useful. Conclusion: Similar field-based research training programmes should be supplemented with separate courses in research meth- odology.